Invert sugar from sugar cane molasses : a pilot plant study - Stolz, Hendrik Nicolaas Petrus (Stellenbosch : University of Stellenbosch, 2008)
An investigation was done into the recovery of invert sugar from sugar cane molasses. A pilot plant was designed and constructed to evaluate the clarification and separation of molasses to produce invert sugar syrup. The aim of the pilot plant was to prove the process and deliver data so as to facilitate the design and prove the financial viability of a commercial plant. The pilot plant had to process 300 kg/day of molasses. The clarification of molasses by centrifugal separation, a known desludging process, did not produce a product of acceptable quality which could be used in a chromatographic separator. The results were disappointing. The product obtained was also not suitable for dead end pressure filtration. The turbidity remaining after the centrifugal separation also did not respond to a second flocculation process. Conventional settling clarification was investigated. Seven factors that could influence the consolidation and settling of suspended solids in molasses were identified, namely: the age of the diluted molasses, the temperature of the flocculated mixture, the variations across various batches of flocculant, the effect of reaction time of the phosphoric acid, the optimum flocculant dosing concentration, the optimum concentration of the molasses solution and the effect of increasing the acid dosage. The optimum conditions to clarify molasses through settling were found to be: fresh molasses, at 28 Brix and 60°C, allowing 10 min intervals between acidification with 3,75 g (as 100%) phosphoric acid/ kg dry material (assumed equal to Brix) and neutralisation with 5 g (as 100%) caustic/kg dry material (assumed equal to Brix), flocculation with any batch of flocculant 6195, dosed as a 1000 ppm solution. Commercial equipment was evaluated. The pilot plant E-cat clarifier was operated at 300 l/h and a thick sludge formed. The overflow was clear and it could be filtered. The molasses obtained was suitable for chromatographic separation. The recovery of sugars from molasses sludge has economic merit. From the evaluation of centrifugal separation and gravity separation it is clear that gravity separation again is the best method. The sweet-water obtained is consistent within the clarity requirement of 10 NTU/Brix and can be used to dilute raw molasses in the upstream processing step. The clarification process that was developed is patented. [Bekker, Stolz et.al. (2001)] A sugar recovery of 93.9 mass % at a purity of 99.7 mass % from molasses, was achieved using a simulated moving bed, ion exclusion, pilot plant. The operating conditions for this performance were: feed flow at 14 l/h and at a temperature above 60 °C; water flow at 63 l/h and at a temperature above 65 °C; extract flow at 21 l/h; raffinate flow at 56 l/h; loop flow at 78 l/h and step time at 1326 seconds. This relates to the following bed volumes of the various separation zones: Bed Volume Zone 1 = 0.694; Bed Volume Zone 2 = 0.591; Bed Volume Zone 3 = 0.661; Bed Volume Zone 4 = 0.383. There is a trade-off between purity and recovery and a reduction in water usage. A preliminary environmental impact assessment and conceptual mass balance were done. The proposed plant integrates well into the existing Komati Mill of TSB and does not pose any significant environmental threat. The plant requires certain services from the mill. The mass balance investigated the water and steam consumption of the plant. Process integration was done so as to obtain the optimum utility consumption. The utility consumption of the plant does not exceed the capacity available at the mill. A small boiler is however required to produce steam during the annual mill maintenance period. Various techniques were used in a cost estimation for the invert sugar plant. The internal rate of return (IRR) is 42% for a fixed capital investment of R94,270,000.00. The net return rate (NRR) for the project is 4%/year, the net present value (NPV) - discounted at a 30% cost-of-capital is R41,782,000.00. The net payout time (NPT) is 5.207 years. The project fulfils the financial requirements set by TSB. It is now possible and viable to desugarize cane molasses.